Объяснение:
1 . 5) ( x + 1 )/(x²- xy ) i ( y - 1 )/(xy - y²) ;
y*(x + 1 )/xy(x - y ) i x*(y - 1)/xy(x - y ) ;
6) 6a/(a - 2b) i 3a/( a + b ) ;
6a( a + b )/(a + b)(a - 2b ) i 3a(a - 2b)/(a + b)(a - 2b ) ;
7) ( 1 + c²)/( c² - 16 ) i c/( 4 - c ) ;
( 1 + c²)/( c² - 16 ) i - c(c + 4 )/( c² - 16 ) ;
8) ( 2m + 9 )/(m² + 5m + 25 ) i m/(m - 5 ) ;
(2m + 9 )(m - 5)/(m - 5)(m²+5m +25 ) i m( m²+5m +25 )/(m - 5)(m²+5m +25 ).
а) z* = -z·i
z = x + iy
x - iy = -(x + iy)·i
x - iy = -ix + y
x + ix = y + iy
x·(1 + i) = y·(1 + i)
y = x
z = x + ix, x ∈ R
б) 2·|z| - 8z + 1 + 2i = 0
z = x + iy
2√(x² + y²) - 8·(x + iy) + 1 + 2i = 0
2√(x² + y²) - 8x - i8y + 1 + 2i = 0
2√(x² + y²) = (8x - 1) + i(8y - 2)
2√(x² + y²) = 8x - 1
8y - 2 = 0
y = 1/4
2√(x² + (1/4)²) = 8x - 1
4(x² + 1/16) = 64x² - 16x + 1
8x - 1 ≥ 1/2
4x² + 1/4 = 64x² - 16x + 1
8x ≥ 3/2
60x² - 16x + 3/4 = 0
x ≥ 3/16
240x² - 64x + 3 = 0
D = 64² - 4·240·3 = 1216
x = (64 (+/-) √1216)/480 = (64 (+/-) 8√19)/480 = (8 (+/-) √19)/60
x = 2/15 (+/-) √19/60
x ≥ 3/16
x = 2/15 + √19/60
z = 2/15 + √19/60 + i/4
2) a2b-4b3/3ab2*a2b/a2-2ab = b(a2-4b)/3ab2 * a2b/a(a-2b)= (a-2b)(a+2b)/3a(a-2b)=
a+2b/3a
3) x2-xy/x2+xy × x2y + xy2/xy = x(x-y)/x(x+y) * y= y(x-y)/x+y